Recommendations and optimal approaches to robotic-assisted partial nephrectomy: A consensus of Brazilian experts - Faria, Eliney Ferreira; Moschovas, Marcio Covas; Vaz, Carlos; Pompeo, Alexandre; Santos, Alexandre; Stievano, Alexandre; Berger, Andre; Carneiro, Arie; Dourado, Aurus; Colombo, Jose Roberto; Passerotti, Carlo; Andreoni, Cassio; et al. (Frontiers in Urology, 2023)
Objective: Robotic-assisted partial nephrectomy (RAPN) is established as the gold standard approach to treating small renal masses. However, numerous technical challenges and concepts related to this approach are still under discussion and are not consensus among surgeons from different centers. We performed an online questionnaire with multiple topics about RAPN and selected high-volume surgeons from referral centers in Brazil to achieve a consensus. Methods: We implemented an online consensus of 29 experts selected based on surgical expertise and competence in analyzing the published literature. Based on the collected literature and current Guidelines (NCCN, AUA, and EAU) we created a questionnaire with 131 questions and administered it to all participants. The statements and the Delphi technique design were combined in a single round of questions. The answers were reviewed, 70% of concordance was considered a consensus, and a final manuscript with recommendations was developed. Results: We divided our results into 25 subtopics that included all questions and discussions of the questionnaire, including preoperative settings, surgical technique, pathological analysis, technology use, and challenging cases. Some areas had limited data in the literature, and these potential limitations were addressed and discussed on each topic. Conclusion: RAPN is the standard surgical treatment for renal masses in the centers of robotic surgery. Among the important topics of this study, we recommend always performing the first RAPN cases with proctors’ assistance, conducting preoperative planning using good-quality imaging exams, minimizing the amount of renal parenchyma removed, and achieving appropriate hemostatic suture while reducing renal parenchyma ischemia.